Postovipositional development of the sand snake Psammophis sibilans (Serpentes:Lamprophiidae) in comparison with other snake species. (13th January 2016) - Khannoon, Eraqi R.; Zahradnicek, Oldrich
Abstract: Characterizing and comparing developmental progress across different species helps to interpret how different or similar body forms evolved. We present an embryonic table for the oviparous African Sand Snake Psammophis sibilans from the Lamprophidae family, describing its postovipositional in ovo development. Psammophis is a good model of a genus that is widely distributed in Africa and Asia and includes 22 species. We describe ten embryonic stages based on the development of externally visible morphological characteristics such as; pharyngeal arches, facial processes, eyes, scales, body pigmentation and body colour pattern development. This study discusses the development of this snake and compares it with that of the closely related brown house snake Lamprophis fulliginosus (Lamprophidae) and the medically important venomous cobras Naja haje haje and Naja kaouthia from the sister lineage Elapidae. The distantly related basal snake Python sebae, which displays different morphology and behaviour, was chosen for deeper insight into the evolution of body structures within the snake clade. We found interspecific differences in the relative stage of development of embryonic structures at the time of oviposition and during postovipositional embryonic development. One of the outcomes of this study is that embryonic structures such as the pharyngeal processes, eye pigmentation and scales are interspecifically conservative in regard to timing of morphodifferentiation, while body pigmentation, colour and colour pattern are interspecifically plastic in their temporospatial development.